Impact of neuromuscular electrical stimulation on functional capacity of patients with chronic kidney disease on hemodialysis - Roxo,Renata Spósito (2016)
Abstract Introduction: Literature shows that patients undergoing hemodialysis present poor physical conditioning and low tolerance to exercise. They may also suffer from respiratory dysfunctions. The purpose of this study was to evaluate the effects of neuromuscular electrical stimulation on pulmonary function and functional capacity of patients with chronic kidney disease on hemodialysis. Methods: Forty adult patients with chronic kidney disease on hemodialysis were prospectively studied and randomized into two groups (control n = 20 and treatment n = 20). The treatment group underwent bilateral femoral quadriceps muscles electrical stimulation for 30 minutes during hemodialysis, three times per week, for two months. The patients were evaluated by pulmonary function test, maximum respiratory pressures, maximum one-repetition test, and six-minute walk test (6MWT), before and after the treatment protocol. Results: The treatment group presented increased maximum inspiratory (MIP) (p = 0.02) and expiratory pressures (MEP) (p < 0.0001), muscular strength in maximum one-repetition test (p < 0.001), and distance covered in the 6MWT (p = 0.03), and decreased systolic blood pressure (p < 0.001) and respiratory frequency (p < 0.001) when compared with the control group. Conclusion: Electrical neuromuscular stimulation had a positive impact on pulmonary function and functional capacity, leading to better physical performance in patients on hemodialysis.